2021
DOI: 10.1186/s12891-021-04376-5
|View full text |Cite
|
Sign up to set email alerts
|

Intra-and interobserver reliability of determining the femoral footprint of the torn anterior cruciate ligament on MRI scans

Abstract: Background Re-injury rates following reconstruction of the anterior cruciate ligament (ACL) are significant; in more than 20% of patients a rupture of the graft occurs. One of the main reasons for graft failure is malposition of the femoral tunnel. The femoral origin of the torn ACL can be hard to visualize during arthroscopy, plus many individual variation in femoral origin anatomy exists, which may lead to this malpositioning. To develop a patient specific guide that may resolve this problem,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Finally, 22 patients were in the good position group, 62 patients were in the poor position group, and the rate of good bone tunnel position was only 26.2%. Moloney et al showed that if only depending on bone landmarks, the femoral positioning site might be deviated by > 2.5 mm from the original footprint center by more than half of surgeons, indicating that the positioning by intra-articular bone landmarks was not reliable [ 9 , 15 , 21 ]. The findings were in agreement with the results of the present study, which showed that the positions of femoral tunnels were not concentrated, and the rate of good bone tunnel position was low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 22 patients were in the good position group, 62 patients were in the poor position group, and the rate of good bone tunnel position was only 26.2%. Moloney et al showed that if only depending on bone landmarks, the femoral positioning site might be deviated by > 2.5 mm from the original footprint center by more than half of surgeons, indicating that the positioning by intra-articular bone landmarks was not reliable [ 9 , 15 , 21 ]. The findings were in agreement with the results of the present study, which showed that the positions of femoral tunnels were not concentrated, and the rate of good bone tunnel position was low.…”
Section: Discussionmentioning
confidence: 99%
“…Of these factors, bone tunnel is an important influencing factor. During the surgical procedures of ACL reconstruction, various femoral tunnel positioning methods have already been discovered [ 2 9 ]. However, none of the methods are suitable for all the conditions, and no single method can be recommended to treat all types of diseases; instead, suitable methods should be selected according to the lateral femoral wall.…”
Section: Introductionmentioning
confidence: 99%
“…Using the Mimics Innovation Suite Software version 21.0 (Materialise, Leuven, Belgium), the images were segmented to obtain accurate 3D models of the knee. The MRI images were semi-automatically segmented with the use of the livewire technique as previously described [ 29 ]. Using this technique, the software is able to semi-automatically distinguish different gray scales in order to select a region of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that the identification of the femoral insertion using this method has a high intra- and interobserver reliability, even in the presence of ACL injury [ 29 ]. Intra-observer reliability for this method has been shown to be excellent with an ICC of > 0.98 and excellent interobserver reliability with an ICC of > 0.96.…”
Section: Methodsmentioning
confidence: 99%
“…This constraint will affect the inter-and intra-observer reliability in genitourinary case diagnosis. The kappa value was used to conduct reliability tests, which included inter-observer (agreement between two observers & agreement between separate observers) and intra-observer (agreement between one observer experiences when observing the same case or more than once) (2,3,15). It might be difficult for the observer to make an accurate diagnosis in the absence of clinical history, thus reduce the reliability of slide observers to report cases (4,16).…”
Section: Introductionmentioning
confidence: 99%